Key Issues for Management of Innovative Projects - Llamas Moya, Bernardo; Dolores Storch de Gracia, M.; Mazadiego, Luis F. (IntechOpen, 2017)
This book gathers pioneering experiences based on the same concept: innovation. According to Schumpeter's research, there would be four types of innovations: product or service innovation (market introduction of a new type of good), process innovation (introduction of a new type of production), market innovation (introduction of a new market in a country or a new market structure), and innovation of matter (introduction of a new raw material). This book contains ten chapters organized in four main sections: (a) "Strategic Issues," (b) "Risk Management in Innovative Projects," (c) "Economic Issues and Financing Innovation," and (d) "Leadership and Teamwork."